A novel near-infrared colorimetric probe for fluoride anions based on a heptamethine dye. Issue 34 (16th August 2016) - Jin, Di; Zhao, Xu; Li, Yang; Yan, Xilong; Chen, Ligong
Abstract : A new colorimetric probe for rapid, selective and sensitive detection of fluoride anions was reported. Abstract : A near-infrared heptamethine indocyanine probe was successfully synthesized and demonstrated to be a colorimetric and fluorescent probe for F − with high selectivity and sensitivity. In the presence of F −, the probe shows a new prominent absorption peak at 942 nm, accompanied by a remarkable solution color change from pale red to colorless in a few seconds, which provides a way for the 'naked-eye' detection of fluoride anions. These responses were attributed to the deprotonation of the –NH fragment of an indolyl unit, and the 1 H NMR study and density functional theory (DFT) calculations are in agreement with them. Moreover, the probe can be employed to detect F − quantitatively within a certain concentration range, and the limit of detection could be as low as 1.3 μM.